2023
DOI: 10.3389/fimmu.2023.1170443
|View full text |Cite
|
Sign up to set email alerts
|

Fueling the flames of colon cancer – does CRP play a direct pro-inflammatory role?

Abstract: BackgroundSystemic inflammation, diagnostically ascribed by measuring serum levels of the acute phase reactant C-reactive protein (CRP), has consistently been correlated with poor outcomes across cancer types. CRP exists in two structurally and functionally distinct isoforms, circulating pentameric CRP (pCRP) and the highly pro-inflammatory monomeric isoform (mCRP). The aim of this pilot study was to map the pattern of mCRP distribution in a previously immunologically well-defined colon cancer (CC) cohort and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Additionally, mCRP expression was significantly associated with tumor-infiltrating neutrophils, similar in that respect, to our study. The macrophages distributed in tumoral areas showed less mCRP positivity, compared with our results, suggesting that mCRP might just be an amplifier of the local inflammatory response in this case [20]. We consider that a correlation between the consistent data offered by this study with an extension of our study to a larger cohort of IBD patients could provide a novel mechanistic understanding of the risk of developing IBD-related neoplasia in patients with UC and CD.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Additionally, mCRP expression was significantly associated with tumor-infiltrating neutrophils, similar in that respect, to our study. The macrophages distributed in tumoral areas showed less mCRP positivity, compared with our results, suggesting that mCRP might just be an amplifier of the local inflammatory response in this case [20]. We consider that a correlation between the consistent data offered by this study with an extension of our study to a larger cohort of IBD patients could provide a novel mechanistic understanding of the risk of developing IBD-related neoplasia in patients with UC and CD.…”
Section: Discussionsupporting
confidence: 68%
“…In cardiovascular and neurovascular diseases and in the tumoral pathology of the colon, mCRP was stained in endothelial cells, supporting the hypothesis that these cells are targeted for the dissociation of pCRP into mCRP, with perhaps a critical contribution to the localization of the inflammatory response [ 20 - 25 ]. In our study, and in contrast, mCRP was expressed only in intravascular inflammatory cells, without association with vascular endothelium suggesting at least partially a nonsystemic source and likely in situ precipitation.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Moreover, in vitro experiments have shown that mCRP decreases the uptake of acetylated LDL by human umbilical vein endothelial cells (HUVECs) [ 76 ]. Nevertheless, some of the studies that investigated the effects of CRP on LDL uptake and foam cell formation did not distinguish between the different isoforms of CRP, even though the bioactivity of CRP is known to depend on its structural status [ 7 , 8 , 9 ]. A few studies have purposely distinguished between the pCRP and mCRP isoforms, but these have also reported somewhat controversial findings [ 60 , 65 , 76 ].…”
Section: Foam Cell Formation and The Degradation Of Extracellular Matrixmentioning
confidence: 99%
“…This is formed at local inflammation sites as a consequence of pCRP dissociation. In contrast to pCRP, mCRP is mostly tissue bound and has significantly lower aqueous solubility [ 8 , 9 ]. There are also structures consisting of partially dissociated pCRP existing as membrane-bound intermediates (described as mCRP m or pCRP*), which act similar to mCRP.…”
Section: Introductionmentioning
confidence: 99%